The simulation of transient fatigue in rugby league - Highton, J.; Mullen, T.; Twist, C. (27th Annual Congress of the European College of Sport Science (ECSS), Sevilla, 30. Aug - 2. Sep 2022, 2022)
INTRODUCTION: Transient fatigue, defined as a temporary reduction in the ability to maintain high-intensity running, is a common phenomenon in team sports [1]. In rugby league, this transient fatigue is also accompanied by reduced skill quality, which could have important implications for match outcomes [2]. The large match-to-match variability in running metrics in rugby league has meant that simulation protocols are often used to explore changes in performance owing to an intervention. However, to our knowledge, no simulation has attempted to replicate transient fatigue. Accordingly, the aim of this study was to determine if rugby league transient fatigue can be simulated, and whether this fatigue is associated with a reduction in skill.